Assessment of Perfluorinated Alkyl Compound Levels in Soil, Water, and Designated Dump Sites in Damaturu, Nguru, and Gashua - Abba Sidi, Yagana; Musa Lawan, Mohammed (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Perfluoroalkyl substances are detrimental contaminants that differ in several ways from most other well-studied organic chemicals found in everyday products. Perfluorooctanoic acid (PFOA) is one of the perfluoroalkyl substances that affect humans and is commonly found in almost all ramifications of life. The most common route of encounter of PFOA by humans is through washing and wearing of domestic utensils and other industrial chemicals such as surfactants into soil and water. This study assessed the presence and levels of PFOA in both dumpsite soil and leachate water samples from Damaturu, Nguru, and Gashua towns of Yobe state using Gas chromatographic mass spectrometry (GC-MS). The results revealed the presence of PFOA in sixteen per cent (16%) of the soil samples and six per cent (6%) of the water samples across the locations. These include samples collected from krikasamma, sabon pegi, and bindigari areas in Damaturu; Garbi and bulabulin in Nguru, and then katuzu and sabon gari in Gashua. The PFOAs were identified by retention time matching with standard PFOA and mass spectrometry. The mean concentrations of PFOA were 0.0214pg/g, 0.0035pg/g, 0.0098pg/g, 0.1040pg/g, and 0.0236 pg/g in samples collected from Krikasamma, Sabon Pegi, Garbi, katuzu and sabon gari, respectively. These concentrations were, however, significantly higher than the permissible limit of 0.0007pg/g recommended by the Environmental Protection Agency (EPA.) and therefore may possess toxicity to soil, plants and humans. The findings from this study can serve as a baseline for investigation of source, transport and fate of such potentially toxic compounds that are found in most domestic utensils and firefighting facilities.